Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1980
DOI: 10.2136/sssaj1980.03615995004400050049x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Consistence: Effect of Particle Size

Abstract: Briquets composed of sand (0.05–2.00 mm) silt (0.002–0.05 mm), and clay (<0.002 mm) mixtures were hardest when dominantly clay and/or sand and softest or least hard when dominantly silt. Where soils had equal amounts of clay, those with highest amounts of sand, with one exception, were the hardest. Low surface area of sand requires much less clay “mortar” to cement the fewer sand grains per given volume than do the more numerous, smaller silt particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Another laboratory measure of soil cohesive strength is the modulus of rupture (MOR). Laboratory studies have found that MOR is mostly related to clay content (Ibanga et al , 1980). MIR gives a reasonable prediction of this tensile strength measurement where the soil has been remoulded (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…Another laboratory measure of soil cohesive strength is the modulus of rupture (MOR). Laboratory studies have found that MOR is mostly related to clay content (Ibanga et al , 1980). MIR gives a reasonable prediction of this tensile strength measurement where the soil has been remoulded (Figure 6).…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that soil strength was directly related to the percentage of clay, less strongly so to the percentage of sand, and inversely related to the percentage of silt. Reanalysis of the data of Ibanga et al (1980) (Fig. 8) showed that s was strongly related to the silt/clay ratio.…”
Section: Discussionmentioning
confidence: 97%
“…Plot of the modulus of rupture, s , as a function of the silt/clay content ratio for the data set of Ibanga et al (1980) (solid circles) and the fitted expression (Eq. [17]) (solid line).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drying may take several days depending on humidity and soil type. To get different rupture resistances of the fabricated peds, vary the mixture of a sandy and loamy soil, or sandy and silty‐clay loam soil (Ibanga et al, 1980). Some experimentation may be needed on the proportions of the different soils needed to get the desired rupture resistance.…”
Section: Fragmentsmentioning
confidence: 99%